Observational Study of Variations in Termination of the Common Bile Duct in Human Cadaver - Khan, Laila Farzana; Naushaba, Humaira; Ara, Jubaida Gulshan (Bangladesh Journal of Anatomy, 2015)
Context: The union of the distal portion of the common bile duct and the main pancreatic duct varies. They together may form short common channel or long common channel or may open separately into the second part of the duodenum. So detailed anatomical knowledge is essential for any surgical or endoscopic treatment of this region. Materials and Methods: A cross sectional descriptive type of study was carried out in the department of Anatomy, Sir Salimullah Medical College on sixty two (62) human cadaveric extra hepatic biliary apparatus with pancreatic duct. The samples were collected from unclaimed dead bodies that were under examination in the department of Forensic Medicine of Dhaka Medical College, Dhaka and Sir Salimullah Medical College, Dhaka. The present study was conducted to observe the variations in termination of common bile duct with main pancreatic duct in human cadavers. Results: The common bile duct was found to unite with main pancreatic duct within the duodenal wall in 61.3% cases and outside the duodenal wall in 38.7% cases. Conclusion: The findings of the present study revealed that the termination of the common bile duct varies from individual to individual. DOI: http://dx.doi.org/10.3329/bja.v12i1.22611 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 11-13